2001
DOI: 10.1071/ea00080
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of citrus pulp ensiled with wheat straw and poultry litter for sheep

Abstract: In experiment 1, 4 treatments were prepared consisting of a mixture of chopped wheat straw in different proportions, a fixed proportion of poultry litter and 0, 15, 30 and 45% citrus pulp on a dry matter basis. The mixtures were ensiled for 60 days at room temperature in polythene bags. Ensiling (time effect) resulted in an increase (P<0.001) in titrable acidity level and a decrease in pH in the silage. In titrable acidity, there was an interaction effect (P<0.001) between the levels of citrus pulp and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In their study, inclusion of citrus pulp caused linear decrease in DM, CP, CF (crude fiber) and ash contents of the mixtures, and they concluded that these decreases were mainly attributed to the difference in chemical composition of citrus pulp. Similar results have been reported by Migwi et al (2001) who ensiled fresh citrus pulp with high dry matter agro-industrial waste. Kordi et al (2010a) found that by adding of 6, 12 or 18 g barley grain/kg of CPS, DM of silages significantly increased but ash concentration and pH were not affected.…”
Section: Chemical Composition and Fermentational Propertiessupporting
confidence: 90%
“…In their study, inclusion of citrus pulp caused linear decrease in DM, CP, CF (crude fiber) and ash contents of the mixtures, and they concluded that these decreases were mainly attributed to the difference in chemical composition of citrus pulp. Similar results have been reported by Migwi et al (2001) who ensiled fresh citrus pulp with high dry matter agro-industrial waste. Kordi et al (2010a) found that by adding of 6, 12 or 18 g barley grain/kg of CPS, DM of silages significantly increased but ash concentration and pH were not affected.…”
Section: Chemical Composition and Fermentational Propertiessupporting
confidence: 90%
“…Dry citrus pomace is the best nutritional citrus product for livestock, and it is prepared for feeding all year round. Fresh citrus pomace has a moisture content of 85-88%, so adding moisture-absorbing materials in ensiling it can increase the quality of silage production [90]. The chemical and physical composition of citrus by-products is different depending on the type of fruit and the type of processing in the processing factories [91].…”
Section: Fruit and Vegetable Wastementioning
confidence: 99%
“…They reported higher crude protein content in the silage produced with poultry litter than that produced with the grass hay. Migwi et al [46] ensiled citrus pulp with either straw or poultry litter and reported improved silage fermentation dynamics with these two absorbents. The addition of straw to the beet pulp improved the DM content, WSC, in vitro dry matter digestibility (IVDMD) and increased the fibre fraction of the silage compared to the control.…”
Section: Use Of Absorbents To Improve the Ensiling Of High Moisture Plant By-productsmentioning
confidence: 99%